Loss of the socio-cultural implicit meanings in the English translations of Mu'allaqat - Shaatti, Kamal Chaft; Zainon Hamzah, Zaitul Azma; Md Rashid, Sabariah; Hajimaming, Pabiyah (Islamic Azad University, 2016)
Abstract Translation of literary texts, especially poetry, is one of the most difficult tasks; it requires mastery and knowledge of the language system and culture, and lack of this might lead to wrong translation. This study aimed to examine the loss and gain of the sociocultural implicit meanings in the English translations of the Mu’allaqat, and assess whether the translators of the Mu’allaqat have succeeded or failed in transferring the sociocultural implicit meanings from the source text (ST) to the target text (TT). The study examined four English translations of two poems; namely, Labid’s poem and Tarafa’s poem. The selected poems are considered as masterpieces of the Arabic ancient poetry loaded with cultural signs. This study combined New mark's approach (1988) of translation with Baker’s taxonomy (1992-2011), i.e. translation equivalence, in analysing the data. The findings of the study showed that there are two types of loss made by translators in translating the Mu’allaqat: inevitable loss and avertable loss. The findings also revealed that the loss of socio-cultural implicit meaning occurred because of the inadequate use of the communicative equivalence by the translators and absence of employing pragmatic equivalence.